Mitigating or Magnifying the Harmful Influence of Workplace Aggression: An Integrative Review - Zhong, Rui; Lian, Huiwen; Hershcovis, M. Sandy; Robinson, Sandra L. (Academy of Management Annals, 2023)
As a substantial amount of research has accumulated on the harmful consequences of workplace aggression for target employees, we believe it is now of particular importance to examine moderators that alleviate or amplify these harmful effects. We ask the following questions: For whom is workplace aggression more or less detrimental? Moreover, what can target employees and the organization do to mitigate the harmful effects of aggression? We propose to address these questions with an integrative review of empirical research on moderators of the harmful effects of workplace aggression on targets. In this review, we identify and illustrate five broad perspectives that existing research has primarily used to explain the moderating effects: resource-depletion, social-relational, appraisal, self-regulation, and social-influence perspectives. In addition, we identify a large number of moderators and synthesize them into three categories of individual moderators—trait-based, intrapersonal, and coping-based—and three categories of contextual moderators—collective, interpersonal, and job-based. We address research findings on each category of moderators organized around the theoretical perspectives. We conclude with a general discussion of an overarching summary, redundant and saturated findings, as well as research gaps and future directions.